Application of superconducting fault current limiter in power system / Nur Amalina Abu Samah - Abu Samah, Nur Amalina (2010)
In this paper, an application of superconducting fault current limiter (SFCL) is proposed to limit the fault current that occurs in power system. The unsymmetrical faults are analyzed. The SFCL is incorporated to the bus which gives the highest fault current at two different positions that is the main position and the feeder position. There are two types of SFCL, purely resistive and purely inductive. Simulations were performed using MATLAB Programming and Simulink version 7.5 and were tested on 11 bus IEEE systems to show its capability and feasibility.